Sagot :
Answer:
x² + (y + 5)² = (√68)²
Step-by-step explanation:
(1) State the given
x1 = 0
y1 = -5
x2 = 2
y2 = 3
(2) Solve for the radius using distance formula
[tex]r = \sqrt{(x2 - x1)^{2} + (y2 - y1)^{2} } \\ r = \sqrt{ {(2 - 0)}^{2} + {(3 - ( - 5))}^{2} } \\ r = \sqrt{ {(2)}^{2} + {(3 + 5)}^{2} } \\ r = \sqrt{4 + 64} \\ r = \sqrt{68} [/tex]
(3) Substitute the coordinates of the center (0,-5) and the obtained r value in the standard form of the equation
(x - h)² + (y - k)² = r²
(x - 0)² + (y -(-5)) = (√68)²
x² + (y + 5)² = (√68)²
#CarryOnLearning
>_<